Development of an empirical dynamic simulator for the analysis of control strategies in an autogenous grinding circuit - J. Valenzuela; R. del Villar; M. Bourassa; S. St. Arnaud (Canadian Institute of Mining, Metallurgy and Petroleum, 1995)
"Autogenous grinding is used quite frequently for mineral comminution as a result of its lower capital and operating costs. However, it is more difficult to control than conventional grinding, particularly when the autogenous or semiautogenous mill is the only comminution stage (i.e. no secondary grinding is available). Analysis of the control strategy used then becomes extremely important, a task that is greatly simplified by the use of an empirical dynamic simulator:This paper presents the methodology used in the development and the calibration of such a simulator for the autogenous grinding circuit of an iron are concentrator: The various steps are described: industrial data acquisition, preliminary treatment of the gathered information. and empirical modelling of the process. Finally, both the actual and the proposed control strategies are compared using simulation results.This exercise has shown that the variability of some of the controlled variables could be reduced through a better handling of the water addition and the use of filters on some of the signals used for control purposes. The reduction in variability of critical variables, such as power draw, would allow their average value to be increased without the risk of exceeding their safety values. Some advanced control techniques were also tested, with interesting results."